Marketing-Based Risk Mitigation in the Riyadlul Jannah Orphanage - Elia Resha Fatmawati; Tri Esti Rahayuningtyas; Sisca Dian Rahmawati; Dessy Fatmawati; Nadiya Fikriyatuz Zakiyah (JOCESS : The Journal of Community Empowerment and Sustainability Services, 2025)
Risks can occur at any time, and the risks that are constantly faced by the managers of the Riyadlul Jannah Orphanage feel so complex. Daily or routine risks encountered are the availability of necessities for the needs of foster children: food, washing equipment, bathing equipment, and teaching and learning materials. In addition, the pure risks are the orphanage leaking, flooding, falling trees, burning, and the like. Next is the survival risk, namely the continuity of the implementation of the orphanage social enterprise, the sustainability of foster children after entering the community, and the ability to see every business and marketing opportunity to survive. The method used is the risk mitigation method using the marketing concept with stages: risk identification, risk tabulation, risk priority, and alternative elements of strategies that will be implemented so that the Riyadlul Jannah Orphanage continues to survive and survives and is accepted by the wider community. To maximize the results of community service, the means used are marketing-based risk mitigation using tools on the web. Mitigasiresiko.com is accessed by training participants to gain experience in carrying out risk mitigation by utilizing elements available at the Riyadlul Jannah Orphanage. This paper evaluates the effectiveness and usefulness of the web tool. Mitigasiresiko.com. in supporting the implementation of community service at the Riyadlul Jannah Orphanage.